Transformasi Administrasi Publik Lokal Berbasis Kebijaksanaan Lokal Dalam Mendukung SDGs Melalui Pelayanan Digitalisasi Di Kantor Perdagangan Kabupaten Lombok Tengah - Nasuhi, M.; Mufidah, Mufidah; Yaqutunnafis, Lale; Hadi, Sofian (CV. Dalle’ Deceng Abeeayla, 2026)
Digital-based public administration transformation is a key agenda for achieving effective, efficient, and transparent services at the regional level. However, the implementation of service digitalization at the Central Lombok Regency Trade Office still faces various obstacles, including public digital literacy, apparatus readiness, and uneven technological infrastructure. This study aims to analyze the effectiveness of public service digitalization by considering the socio-cultural context, identifying the integration of local wisdom values ​​into digital administration practices, assessing the level of public participation and trust, and formulating relevant transformation strategies to achieve the Sustainable Development Goals (SDGs). This study uses a qualitative approach with data collection techniques such as in-depth interviews, observation, and documentation, involving Trade Office officials, business actors, and service users. The results show that although digitalization improves efficiency and transparency, its implementation is not fully optimal due to digital literacy gaps, limited infrastructure, and public resistance to online services. Another important finding is the suboptimal integration of local wisdom values, which have significant potential to strengthen public participation and trust. This study concludes that public administration transformation in Central Lombok requires an approach that is not only technological but also contextual, integrating local wisdom into digital systems. This transformation model can be an innovative strategy to strengthen inclusive, responsive, and sustainable public services, while supporting the achievement of the SDGs at the local level.